2010
DOI: 10.1186/1471-2121-11-91
|View full text |Cite
|
Sign up to set email alerts
|

The role of HIF-1 in up-regulating MICA expression on human renal proximal tubular epithelial cells during hypoxia/reoxygenation

Abstract: BackgroundHuman major histocompatibility complex class I-related chain A (MICA) plays a dual role in adaptive and innate immune responses. Increasing evidence demonstrates that MICA is closely correlated with acute and chronic kidney allograft rejection. Therefore, understanding the activation mechanisms of MICA is important in kidney transplantation. We previously demonstrated that ischemia/reperfusion injury (IRI) could up-regulate MICA expression on mouse kidney allografts. Since hypoxia-inducible factor-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…This is in accordance with data showing that HIF-1α is necessary for the hypoxia-induced reduction of the MICA membrane expression on malignantly transformed cells (Barsoum et al 2011;Yamada et al 2012). However, in nontransformed human cells, MICA/B membrane expression was found to be upregulated by a hypoxia/reoxygenationinduced HIF-1α overexpression (Luo et al 2010;Wei et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with data showing that HIF-1α is necessary for the hypoxia-induced reduction of the MICA membrane expression on malignantly transformed cells (Barsoum et al 2011;Yamada et al 2012). However, in nontransformed human cells, MICA/B membrane expression was found to be upregulated by a hypoxia/reoxygenationinduced HIF-1α overexpression (Luo et al 2010;Wei et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…These results show that the effects of hypoxia on the expression of cell surface MICA are mediated by HIF-1α. It has been reported that HIF-1α upregulates the expression of MICA in human renal proximal tubular epithelial cells and cardiomyocytes (25,26). The effects of HIF-1α on the expression of cell surface MICA may be different between tumor cells and normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemia is also intimately associated with tissue hypoxia. Recent work has suggested a role for HIF in the regulation of inflammatory tissue damage that is associated with ischaemic disease in the brain and kidney 126128 .…”
Section: Hypoxia In Pathological Immune Nichesmentioning
confidence: 99%